Improvement of the Legislation of Ukraine as to the Provision of the Protection of Banking in the Conditions of European Integration - KLOCHKO, Alyona M.; KURILO, Nikolai P.; ZAPARA, Svetlana I.; ARISTOVA, Irina V.; LOGVINENKO, Mykola I. (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017, 2017)
Euro-integration course of Ukraine has caused an intensive development of its banking sphere. The inconsistency between the possible legislative consolidation of criminal responsibility for socially dangerous acts in the banking sector and the objective needs of society in such protection becomes more and more obviousis in Ukraine. The processes of ‘clearing’ the banking system from financial institutions that are insolvent along with the positive results have led to an increase in the level of criminalization of the banking sector. Abuses aimed at taking possession of money from creditors and borrowers of banking institutions have become widespread. External threats to the stable functioning of the banking sector are combined with internal misconduct of unscrupulous bank managers, officials and persons related to the banks. Approaches to legislative regulation of suspicious banking transactions and to identify their real volumes must be improved. The measures aimed at reducing of the level of criminalization of the banking sphere by establishing criminal liability of managers and persons connected with the bank for unlawful acts in the banking sector must be taken. The certain issues of legal regulation of banking activity in Ukraine on criminal legal level are considered. The provisions of international law on these matters are  analyzed and the main ways to optimize Ukranian criminal legislation to ensure the safety of banking activity are suggested. It turns out that the need for criminal legal protection of banking is conditoned by an increase in the public danger of these acts at the present stage of the functioning of society. This need is also confirmed by the crisis in the financial and banking spheres of the state, the need to eliminate the gaps in the current legislation on banking safety and the changes that took place in the banking sector of Ukraine in the context of increased integration with the EU.